Study on the progressive collapse behavior of fully bolted RCS beam-to-column connections. (15th November 2019) - Tang, Hongyuan; Deng, Xuezhi; Jia, Yigang; Xiong, Jingang; Peng, Chunmei
Highlights: An asymmetric beam-column connection of RCS frame structure was studied under static loading. The progressive collapse resistance of this RCS frame structure was studied. The progressive collapse resistance of asymmetric structure was compared with that of symmetric structure. The rotational capacity of asymmetric structure was lower than that of symmetric structure. The rotational capacity of this RCS frame structure was higher than the limit of DoD. Some parameters affected the progressive collapse resistance of this RCS frame structure were studied. Abstract: Most of the vertical progressive collapse failure of structures is caused by central-column removal. When the lateral stiffnesses on the two sides of a removed column are different, the structure fails in an asymmetric manner. Thus far, studies on asymmetric progressive collapse have been limited in the existing literature. In this study, an asymmetric double-half-span single-column structure was taken as the research object, and a type of through-column-type beam-column connection substructure was designed with a fully bolted connection in reinforced concrete (RC) column and steel (S) beam (RCS) frame structure. The entire process of the asymmetric collapse and the failure of the structure under the failure of a penultimate column was simulated by a static loading test. The difference between the lateral stiffness of the columns on the two sides of the removed column in the substructure was simulated by the unequal span. Additionally, the mechanism and the failure mode of the connections under progressive collapse were simulated using ABAQUS. The results were compared with those of a traditional symmetrical double-half-span substructure. It was found that the top flange of the beam on the side with smaller lateral stiffness first exhibited local buckling when the fully bolted connection substructure failed. Moreover, the rotational capacity of the connection was less than that under the central-column-removal scenario. The catenary action of the connection could not be fully exerted, which caused the ability of the progressive collapse resistance to be lower than that under the central-column-removal scenario. However, the ultimate rotation angle of the connection obtained from the test and the finite element analysis was higher than the allowable limit in the DoD (Department of Defense) guidelines, indicating that the use of the DoD criteria was conservative in evaluating the progressive collapse resistance of the fully bolted connection of the through-column-type RCS structure. Furthermore, through the parametric analysis of the connection, it was found that enhancing the steel strength was the most effective approach for improving the progressive collapse resistance of the connection. Additionally, the ductility of the critical section of the connection could also be effectively improved by increasing the width of the bottom flange and the diaphragm and the thickness of the beam web.